Parallel implementation of the H.263 videoconferencing standard - Poh, Kok Kiong. (2008)
Video compression is widely used in many multimedia applications. However, there is a continuous need for faster video compression solutions in real time applications, particularly in the encoding procedures of video compression. It is anticipated that the processing speed can be improved with the introduction of parallel processing.